Chitosan-Based Coating Application to Enhance Antimicrobial and Water Vapor Barrier Properties of Industry-Manufactured Paper - Akbarningrum Fatmawati; Natalia Suseno; Emma Savitri; Gloria Tifany Masui; Felia Azzahra Ivony (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Chitosan, a renowned natural polymer for its wide application, was exploited for industry paper coating solutions. This research aimed to investigate the antimicrobial and water vapor barrier of chitosan solution-coated industry-manufactured paper. The papers were obtained from a national company in Indonesia. The commercially available chitosan with three molecular weight levels (low, medium, and high) was solubilized in sodium acetate buffer and subsequently utilized as the coating solution. The other variable studied was the chitosan concentration in the coating solution, i.e., 1.0, 1.5, and 2.0% (w/w). The antimicrobial activity study was performed by testing against Gram-positive bacteria, represented by Staphylococcus aureus, and Gram-negative bacteria, represented by Escherichia coli. The low molecular weight chitosan showed the best antimicrobial activity and water vapor barrier performance. The 1 %w low molecular weight chitosan-coated paper had shown good antimicrobial activity, against both S. aureus and E. coli, with a growth reduction of > 95 %. The most effective antimicrobial activity against S. aureus was achieved by paper coated with a 1.5% solution of low molecular weight chitosan. For low molecular weight chitosan-coated paper the most effective water vapor barrier was exhibited at 1 %w chitosan concentration. Having shown the best water vapor barrier while maintaining good antimicrobial activity, the 1.0% solution of low molecular weight chitosan was appointed as the best coating solution in this research.